2012
DOI: 10.1063/1.3696032
|View full text |Cite
|
Sign up to set email alerts
|

Inertial confinement fusion implosions with imposed magnetic field compression using the OMEGA Laser

Abstract: Experiments applying laser-driven magnetic-flux compression to inertial confinement fusion (ICF) targets to enhance the implosion performance are described. Spherical plastic (CH) targets filled with 10 atm of deuterium gas were imploded by the OMEGA Laser, compare Phys. Plasmas 18, 056703 or Phys. Plasmas 18, 056309. Before being imploded, the targets were immersed in an 80-kG magnetic seed field. Upon laser irradiation, the high implosion velocities and ionization of the target fill trapped the magnetic fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
127
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 42 publications
(32 reference statements)
1
127
1
2
Order By: Relevance
“…16,17 Suppression of the Richtmyer-Meshkov instability, while retaining the effects of shock heating, could be expected to have potentially important consequences for the realization of inertial confinement fusion (ICF). Furthermore, it has been experimentally demonstrated that immersing ICF targets in seed magnetic fields results in an increase in observed ion temperature and neutron yield, 18 which is partially attributed to a reduction in heat losses from the center of the implosion due to electron confinement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Suppression of the Richtmyer-Meshkov instability, while retaining the effects of shock heating, could be expected to have potentially important consequences for the realization of inertial confinement fusion (ICF). Furthermore, it has been experimentally demonstrated that immersing ICF targets in seed magnetic fields results in an increase in observed ion temperature and neutron yield, 18 which is partially attributed to a reduction in heat losses from the center of the implosion due to electron confinement.…”
Section: Introductionmentioning
confidence: 99%
“…This case is of particular interest as the use of a similar magnetic field in ICF experiments, generated by a seed current through an axial thin wire, has been suggested as a means to further enhance electron confinement. 18 In Sec. II we write the equations of motion for non-resistive ideal inviscid magnetohydrodynamics and develop the appropriate characteristic form.…”
Section: Introductionmentioning
confidence: 99%
“…There has been recent interest in the role of applied magnetic fields in high-energy-density plasmas [1][2][3] for inertial fusion energy applications [4]. The MagnetoInertial Fusion Electric Discharge System has been developed to provide steady state magnetic fields for long time-scales relative to the experiments.…”
mentioning
confidence: 99%
“…Sano et al [10] performed a numerical simulation and found that due to the fluid motions associated with the RMI, the ambient magnetic field strength was amplified substantially by an order of two magnitude. Hohenberger et al [11] concluded experimentally that compared to the unmagnetized explosion in ICF, the ion temperature was increased by 15% in the presence of magnetic field, which improved the ICF performance.…”
Section: Introductionmentioning
confidence: 99%